2014
DOI: 10.1111/age.12214
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome haplotype diversity of domestic sheep (Ovis aries) in northern Eurasia

Abstract: Variation in two SNPs and one microsatellite on the Y chromosome was analyzed in a total of 663 rams representing 59 breeds from a large geographic range in northern Eurasia. SNPA-oY1 showed the highest allele frequency (91.55%) across the breeds, whereas SNPG-oY1 was present in only 56 samples. Combined genotypes established seven haplotypes (H4, H5, H6, H7, H8, H12 and H19). H6 dominated in northern Eurasia, and H8 showed the second-highest frequency. H4, which had been earlier reported to be absent in Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 7 publications
3
22
0
Order By: Relevance
“…Several studies have shown that H6 is the most predominant haplotype in different sheep breeds (12,14,(23)(24)(25), except for the Tyrolean Mountain sheep (Austria) and Brown and White Mountain sheep (Germany) that exhibited only the H8 haplotype (12). In this regard, African breeds also showed a higher frequency for the H6 haplotype (66.6%) (13), while in this study the H8 haplotype is the most frequently observed (55.5%).…”
Section: Discussionsupporting
confidence: 47%
“…Several studies have shown that H6 is the most predominant haplotype in different sheep breeds (12,14,(23)(24)(25), except for the Tyrolean Mountain sheep (Austria) and Brown and White Mountain sheep (Germany) that exhibited only the H8 haplotype (12). In this regard, African breeds also showed a higher frequency for the H6 haplotype (66.6%) (13), while in this study the H8 haplotype is the most frequently observed (55.5%).…”
Section: Discussionsupporting
confidence: 47%
“…The gross haplotype diversity of swamp buffalo was 0.308 ± 0.026. This value is close to that of domestic sheep (0 ~ 03849; Zhang et al, 2014), but lower than that of cattle (0.422 ± 0.3; Edwards et al, 2011) and pig (0.491 ± 0.077-0.711 ± 0.118; Iacolina et al, 2016). Our results suggest a low level of Y-chromosome genetic diversity in swamp buffalo.…”
Section: Discussionsupporting
confidence: 64%
“…; Zhang et al . ); these are the Late Bronze Age sample from Saaremaa and the two samples from the medieval towns. The temporal and spatial distance between these specimens means that they could not be close relatives; due to low sample size; however, it is difficult to calculate any fluctuations.…”
Section: Discussionmentioning
confidence: 99%